Customer insights generation at the front end of innovation: an exploration within a medical device company - Grant, Stuart Russell (Cranfield University, 2023)
It is generally agreed that product innovation happens when innovation teams conduct market research to uncover customer needs. It has also been reported that customer needs and customer insights are essential for radical innovation. Over the last 40 years, research into customer needs has defined needs as either articulated or unarticulated, with associated market research methods to uncover needs and insights, such as surveys, questionnaires, observation, interviews, and a repertory grid. Though customer needs are well-defined, customer insights need an adequate definition. Although definitions exist in the marketing and psychology literature, they are unclear or often conflicting within the product innovation field. For example, customer insights are either a separate concept from a need or a component of needs. As such, how both these concepts relate to radical innovation remains unclear. Furthermore, the process of uncovering customer needs has been well defined; conversely, the process that links the uncovering of customer needs and discovering customer insights requires an improved framework. Nevertheless, does understanding the relationship and process between needs and insights matter and warrant being studied? If, as suggested, finding customer needs leads to incremental innovation and customer insights lead to radical innovation, then understanding this is worthwhile. This is because, firstly, for academics, investigating what innovation teams are doing during the front end of innovation (FEI) will allow them to analyse the data from case studies research more effectively. Secondly, practitioners will better appreciate the FEI process and be able to categorise their findings from market research into needs and insights, which will assist with considering the type of innovation being pursued. Therefore, understanding the relationship between a need and an insight is required. A fuller understanding of the process of discovering insights in the FEI is needed. Through a systematic literature review (SLR) and an exploratory case study, the research attempts to investigate this conceptualisation of customer insight in product innovation and understand the relationship between needs and insights. The SLR reviewed the extant literature on the definitions of, the methods used for finding, and the relationship between needs and insights. The exploratory case study investigated the process of discovering customer insight with innovation teams in a global medical technology company. The research had two strands – retrospective and longitudinal. Five retrospective cases were conducted immediately after the FEI had finished: four interviews per case, totalling 20 interviews. Four longitudinal cases followed the FEI for ten months; an interview was conducted with the participants at 1-, 4-, and 10-month intervals throughout the front end process; this totalled 45 interviews with 15 participants from the four cases. In addition to the interview data, documentation was also collected from all nine cases. The data was collected and analysed based on coding from the literature. The research extends the body of literature on customer needs and insights. From a theoretical perspective, the study provides a clearer understanding of the definition of customer needs and insights. It also suggests the relationship between the concepts of need and insight. The framework proposed that discovering insights produces a better understanding of the front end process. This process is iterative, whereby finer needs are uncovered, and deeper insights are discovered as the team further understands the customer and the market research. From a practice perspective, the study assists innovation in better appreciating the interaction of needs and insights. The research also helps product innovation teams better categorise their market research findings into needs and insights that may drive more radical innovations.
Keywords: customer needs; customer insights; front end of innovation; fuzzy front end; FEI; product innovation